2004
DOI: 10.1073/pnas.0405847101
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation of protein phase behavior with a microfluidic formulator

Abstract: We demonstrated a microfluidic device for rapidly generating complex mixtures of 32 stock reagents in a 5-nl reactor. This ''formulation chip'' is fully automated and allows thousands of experiments to be performed in a single day with minimal reagent consumption. It was applied to systematically study the phase behavior of the protein xylanase over a large and complex chemical space. For each chemical formulation that demonstrated a pronounced effect on solubility, the protein phase behavior was completely ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
179
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(180 citation statements)
references
References 31 publications
0
179
0
2
Order By: Relevance
“…The creation and integration of these components represents a more substantial problem than it might seem, but the development of new microfluidic elements, and means to incorporate them into devices, are proceeding. Systems for bioanalysis and separation, [1][2][3] or high-throughput screening 4,5 are already available. We are especially interested in devices to be used in resource poor environments-e.g., in healthcare in developing countries, by first responders and the military, and in analogous problems-where portability and ruggedness are key concerns.…”
Section: Introductionmentioning
confidence: 99%
“…The creation and integration of these components represents a more substantial problem than it might seem, but the development of new microfluidic elements, and means to incorporate them into devices, are proceeding. Systems for bioanalysis and separation, [1][2][3] or high-throughput screening 4,5 are already available. We are especially interested in devices to be used in resource poor environments-e.g., in healthcare in developing countries, by first responders and the military, and in analogous problems-where portability and ruggedness are key concerns.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known and a significant area of research in microfluidics that mixing in microscale geometries is difficult because of the laminar nature of the fluid flows, the associated lack of turbulence, and the resulting reliance on diffusion (21,22). One design that has been used to mix in relatively large microfluidic devices is to use multilayer soft lithography to create pumps and valves and mix fluids by circulating them within a circular channel (23), an approach that has been used, for example, in screening for protein crystallization (24). This technique, however, relies on the supporting pressurization equipment associated with operating many of these pumps simultaneously that limits very high-level parallelization.…”
Section: Resultsmentioning
confidence: 99%
“…Microfluidic devices containing hundreds of valves in close proximity were realised [25]. Devices designed to perform complex protocols such as the automatic processing of nucleic acids [26], the generation of complex mixtures for use in on-chip protein experiments [27] and the synthesis of chemical compounds on-chip [28] were demonstrated. Moreover it was shown that device designs containing repeated elements could conduct experiments in parallel [29].…”
Section: Lab-on-chip Experimentation Platformmentioning
confidence: 99%